Stage-Gate and successful commercializing of novel ingredients in the food and beverage market - Borne Lavoie, Veronica (My University, 2026)
The novel food ingredient market is projected to grow from $33 billion to over $106 billion in the next decade. Commercializing new food ingredients currently requires experts to navigate complex technical, regulatory, and market barriers, often without a structured framework to guide decision-making. This study examines the current literature on ingredient commercialization and integrates it with empirical data collected from a survey of senior industry professionals with direct experience launching novel food ingredients. Twenty qualified respondents across regulatory, innovation, R&D, manufacturing, business development, and executive leadership roles completed an anonymous 26-question survey covering stage-based risk, failure drivers, decision gates, and key performance indicators. Findings indicate that commercialization risk is not evenly distributed across stages. Downstream adoption emerged as the highest-risk stage and the primary determinant of success, followed by regulatory strategy and manufacturing scale-up. First customer adoption was identified as the single most critical success factor, while time to scale was consistently underestimated across respondents. In addition, organizational misalignment and weak downstream demand were identified as perceived leading root causes of failure, exceeding technical or capital-related constraints. Securing downstream customer commitment and achieving regulatory clarity were consistently identified as the most critical decision gates, reinforcing that commercialization success is driven more by market-adoption readiness than by technical validation alone. To address the lack of a structured commercialization strategy, this study develops and applies the Hazard Analysis and Critical Control Point (HACCP) framework, traditionally used in food safety, as a stage-based model for managing commercialization risks. By identifying the critical control points across developmental stages, a HACCP approach provides a systematic way to monitor, mitigate, and manage commercial risks. The proposed framework, based on pilot study and not inferring broader conclusions, offers a practical tool for improving decision-making and increasing the likelihood of successful market adoption of novel food ingredients.
Keywords: Novel ingredients; Stage Gate; Commercialization; HACCP; Innovation; Launching